Pathways Linking Climate Change to Advanced HIV Disease: A Narrative Review - Kurniawan, Dicky Endrian; Rifai, Ahmad; Afandi, Alfid Tri; Khamid, M. Nur (Health Access Journal, 2026)
Climate change has emerged as a major global health challenge that may worsen HIV-related outcomes through biological, psychosocial, socioeconomic, and healthcare-related mechanisms. This narrative review aimed to synthesize current evidence on the pathways linking climate change to advanced HIV disease (AHD) and to develop a conceptual framework explaining these interactions. A literature search was conducted in the Scopus database for articles published between 2010 and 2025. Studies addressing the relationship between climate change and HIV-related outcomes, including disease progression, ART adherence, food insecurity, migration, psychosocial stress, and healthcare access, were included and synthesized narratively. Relevant studies were screened and synthesized thematically into major pathways, including biological effects, healthcare disruption, food insecurity, psychosocial stress, migration, and social determinants of health. The findings indicate that climate change contributes to HIV progression through direct biological mechanisms, including oxidative stress, NF-κB activation, immune dysregulation, and HPA axis dysfunction. In addition, indirect socioecological pathways, including disrupted ART access, malnutrition, poverty, migration, and psychosocial stress, further accelerate immune suppression and increase morbidity and mortality among people living with HIV. Climate-adaptive HIV care, resilient healthcare systems, nutrition-sensitive interventions, and interdisciplinary public health strategies are urgently needed to reduce climate-related HIV vulnerabilities